Toward a Theory of Career Motivation - London, Manuel (Academy of Management Review, 1983)
Career motivation is viewed as a multidimensional construct. Components consist of individual characteristics (career identity, career insight, and career resilience domains) and corresponding career decisions and behaviors. Relationships among these components and relevant situational conditions are proposed in a model based on prospective and retrospective rationality.